Robert v. Gustin, ed., The Revised Municipal Code of East St. Louis of 1908 Passed March 23, 1908 Approved March 25, 1908 Published by Authority of the City Council in Book Form, June 20, 1908: Containing All the General Ordinances of the City in Force June 20th, A. D. 1908, Together with an Appendix Containing Certain Special Ordinances Granting Franchises to the Various Public Utility Corporations (East St. Louis, IL: East St, Louis Publishing Company, 1909), 361. Chapter 39—Misdemeanors, Article 1—Offenses Affecting the Public Peace and Quiet, §§ 887 - (:unkn) unknown (General Publisher, 1908)
Prohibited firing or discharging any gun, pistol, or other firearm within city limits. Violators fined not more than twenty-five dollars for each offense.
--
Keywords: DISCHARGE